2017
DOI: 10.3835/plantgenome2016.07.0058
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Analysis of Soybean LATERAL ORGAN BOUNDARIES Domain‐Containing Genes: A Functional Investigation of GmLBD12

Abstract: Plant-specific LBD (LATERAL ORGAN BOUNDARIES Domain) genes play critical roles in various plant growth and development processes. However, the number and characteristics of LBD genes in soybean [Glycine max (L.) Merr.] remain unknown. Here, we identified 90 LBD homologous genes in the soybean genome that phylogenetically clustered into two classes (I and II). The majority of the GmLBD genes were evenly distributed across all 20 soybean chromosomes, and 77 (81.11%) of them were detected in segmental duplicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 103 publications
(148 reference statements)
3
31
0
Order By: Relevance
“…In this study, we identified 126 BnLBD genes in B. napus. These BnLBD genes were divided into two groups and ten subgroups based on the evolutionary relationships, which is highly consistent with the reports in Arabidopsis, G. max, and Z. mays [1,6,12]. The variations in the structure of BnLBDs might be because of the gain or loss of introns/exons in the long-term evolutionary process.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, we identified 126 BnLBD genes in B. napus. These BnLBD genes were divided into two groups and ten subgroups based on the evolutionary relationships, which is highly consistent with the reports in Arabidopsis, G. max, and Z. mays [1,6,12]. The variations in the structure of BnLBDs might be because of the gain or loss of introns/exons in the long-term evolutionary process.…”
Section: Discussionsupporting
confidence: 80%
“…WGD/segmental duplication is very common in plant genomes, as most plants have undergone polyploidy events during evolution, and thus retain many duplicated chromosome segments in their genomes [50,51]. Compared with other plant species such as Arabidopsis, O. sativa, Z. mays, G. max, and Populus, which contain 43,35,44,80, and 57 LBD genes [1,6,12,13], respectively, we found B. napus with the largest number of LBD genes, indicating the genome duplication during evolution of B. napus greatly contributed to the diversification of BnLBDs. Further, all 126 BnLBD genes were identified as the result of gene duplication, 93 of them were identified with WGD or segmental duplications history, and the rest resulted from dispersed duplications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LBD genes comprise a plant-specific transcription factor family, which had been proven to have essential roles in the regulation of lateral organ development and metabolic processes, such as anthocyanin and nitrogen metabolism in higher plants (Iwakawa et al 2002;Shuai et al 2002;Majer and Hochholdinger 2011). Comprehensive analyses of this gene family had been conducted in many species such as Arabidopsis (Liu et al 2005), Eucalyptus grandis (Lu et al 2018), Brassica rapa (Huang et al 2018), grapevine (Grimplet et al 2017), soybean (Yang et al 2017), and Camellia sinensis (Teng et al 2018). However, no systematic study of LBD genes has been conducted in allotetraploid cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the MdLBD13 protein can inhibit anthocyanin synthesis and nitrogen uptake in apple (Li et al 2017). Genome-wide analysis of LBD gene family have been studied in plants like Camellia sinensis (Zhang et al 2019), Solanum tuberosum (Liu et al 2019), Eucalyptus grandis (Lu et al 2018), Brassica rapa (Huang et al 2018), grapevine (Grimplet et al 2017), and soybean (Yang et al 2017). However, the function of the LBD genes in Gossypium remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%